Case Report: HSV-2 Encephalitis Presenting With Chorea; Effects of Infection Alone or Combination of Infection and Autoimmunity? - Kolesnik, Michael; Ballout, Ahmad A.; Hameed, Natasha; Najjar, Souhel (Frontiers in Neurology, 2021)
Background: Chorea as a symptom of late-onset post-infectious autoimmune encephalitis has been reported with HSV-1 but not HSV-2 encephalitis. Extrapyramidal symptoms are typically associated with the presence of anti-NMDA receptor antibodies but may also exist in antibody-negative individuals. Case: This case highlights a patient who presented with mental status changes and chorea as the initial manifestation of HSV-2 encephalitis. The choreiform movements failed to respond to antiviral medications but were rapidly responsive to plasmapheresis, which, together with abnormal intrathecal immunoglobulin synthesis, suggests a potential contribution of parainfectious immune-mediated process. The patient made a full recovery and a complete resolution of the chorea. Discussion: This is the first case associating HSV-2 encephalitis presentation with chorea. The neurological complications, including chorea, are largely related to active CNS HSV-2 infection, possibly together with triggered CNS autoimmunity despite undetectable CSF neuronal autoantibodies and normal neuroimaging. Early diagnosis and treatment with antiviral agent and immune therapies might be pivotal to optimize the clinical outcome.